Participant-level characteristics differ by recruitment setting when evaluating a behavioral intervention targeting adolescents with asthma. (4th March 2021) - Joseph, Christine L. M.; Mahajan, Prashant; Buzzelli-Stokes, Stephanie; Jacobsen, Gordon; Johnson, Dayna A.; Duffy, Elizabeth; Williams, Renee; Havstad, Suzanne; Zoratti, Edward; Ownby, Dennis R.; Johnson, Christine Cole; Lu, Mei
Abstract: Objective: The recruitment setting plays a key role in the evaluation of behavioral interventions. We evaluated a behavioral intervention for urban adolescents with asthma in three randomized trials conducted separately in three different settings over the course of 8 years. We hypothesized that characteristics of trial participants recruited from the ED and clinic settings would be significantly different from that of youth participating in the school-based trials. The intervention evaluated was Puff City, a web-based program that uses tailoring to improve asthma management behaviors. Methods: The present analysis includes youth aged 13–19 years who reported a physician diagnosis of asthma and symptoms at trial baseline. In the three trials, all participants were randomized post-baseline to a web-based, tailored intervention (treatment) or generic web-based asthma education (control). Results: Compared to school-based trial participants, ED participants had significantly more acute-care visits for asthma ( p  < 0.001) and more caregiver depression ( p  < 0.001). Clinic-based participants were more likely to have computer/ internet access than participants from the school-based trial ( p  < 0.001). Both ED and clinic participants were more likely to report controller medication ( p 's < 0.001) and higher teen emotional support ( p 's < 0.01) when compared to the schools, but were less likely to report Medicaid ( p 's < 0.014) and exposure to environmental tobacco smoke ( p  < 0.001). Conclusion: Compared to participants in the school-based trials, participants recruited from ED and clinic settings differed significantly in terms of healthcare use, as well as psychosocial and sociodemographic factors. These factors can inform intervention content, and may impact external validity of behavioral interventions for asthma.